Multi-User Virtual System for Training of the Production and Bottling Process of Soft Drinks. - Bermeo Calle, David Andrés (2021)
The project consists of developing a virtual operational training system for the production and bottling process carried out in the soft drinks factory. For the virtualization of the industrial process, mathematical modeling is considered using a transfer function of the first order with downtime and control in relation to the flow plants that make up the substance mixing station in the company, for this, dynamic data and behaviors of the fully automated flow plants within the university are used and not the conventional station existing in the company, since its machines and data are kept confidential In addition, 3D CAD design techniques, electric diagrams of the process and instrumentation (P&ID) are used, all in order for multiple users to have immersive experiences sensory and can interact with each other within a virtual environment.